I can hear the sun : a modern myth - Polacco, Patricia (New York : Philomel Books, 1996)
Stephanie Michelle, who cares for animals and listens to the sun, believes the homeless child, Fondo, when he tells her that the geese have invited him to fly away with them.
Keywords: Homeless persons -- Fiction; Geese -- Fiction; Listening -- Fiction; Sun -- Fiction